Assessment of Selected Properties of Finger Millet (Eleusine coracana L.) Flours as Influenced by Fermentation Period - Benedict Ekhaegba Alabi; Johnson Akinwumi Adejuyitan; Victoria Funmilayo Abioye (Food ScienTech Journal, 2025)
Finger Millet (FM) is an important cereal with high nutritional value. However, it is underutilized due to its small grain size and the presence of anti-nutritional factors. Therefore, this study determined the effect of fermentation period on selected properties of finger millet. Finger millet grains were cleaned, washed and fermented for 0, 24, 48 and 72 h at room temperature (27±2oC), and samples were taken at each of the fermentation periods respectively. Proximate, mineral, anti-nutritional, functional, and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity of the fermented finger millet flour were determined. Analyses reported in this study were carried out in triplicates and data obtained were reported as mean ± standard deviation. Data obtained were subjected to one-way analysis of variance, and significant means were separated using Duncan’s New Multiple Range Test at p